Разработка модели представления компетенций в проектах обучения - Колесников, Алексей Евгеньевич; Лукьянов, Дмитрий Владимирович; Васильева, Валентина Юльевна (НТУ "ХПИ", 2016)
Ценностными направлениями образования являются расширение доступности, массовости образования, гарантий обеспечения равных шансов на получение полноценного образования, создание системы непрерывного образования. Особенно эти ценностные ориентации образования важны для людей, которые уже работают и не имеют возможности посещать очные занятия. На основании системного анализа образовательной деятельности вузов для поддержки процессов дистанционного образования определено множество ключевых параметров и функциональных подсистем, которые в совокупности обеспечивают эффективность проекта построения информационной среды ВУЗа.

Value orientation of education is to expand its accessibility and the creation of a system of continuous education in the form of automated learning systems. Solution of the problem of individualization of learning is only possible in the case of kompetentsnostnogo approach allows you to structure the courses in the form of a minimum set of educational elements that form the basic knowledge and skills of students. To form the competences necessary to make a set of disciplines, with mandatory release of interdisciplinary connections. Formation of competences takes place on the basis of not only the relationship between the disciplines, and the general knowledge of the subject area. The paper deals with the structural model of relations between the competences of the national standard in Ukraine. It is shown that the relationship between the competencies objectively exist and can be used for the formation of a set of competences for which all the elements are interconnected and thus form a set of interrelated elements - the core of competences.
Development of a model representation of competencies in education projects
Keywords: управление проектное; знания; образование высшее; школа высшая; среда информационная; стандарт национальный; training model; knowledge; competence matrix